Cell-free production of personalized therapeutic phages targeting multidrug-resistant bacteria. Issue 9 (15th September 2022) - Emslander, Quirin; Vogele, Kilian; Braun, Peter; Stender, Jana; Willy, Christian; Joppich, Markus; Hammerl, Jens A.; Abele, Miriam; Meng, Chen; Pichlmair, Andreas; Ludwig, Christina; Bugert, Joachim J.; et al.
Summary: Bacteriophages are potent therapeutics against biohazardous bacteria, which rapidly develop multidrug resistance. However, routine administration of phage therapy is hampered by a lack of rapid production, safe bioengineering, and detailed characterization of phages. Thus, we demonstrate a comprehensive cell-free platform for personalized production, transient engineering, and proteomic characterization of a broad spectrum of phages. Using mass spectrometry, we validated hypothetical and non-structural proteins and could also monitor the protein expression during phage assembly. Notably, a few microliters of a one-pot reaction produced effective doses of phages against enteroaggregative Escherichia coli (EAEC), Yersinia pestis, and Klebsiella pneumoniae . By co-expressing suitable host factors, we could extend the range of cell-free production to phages targeting gram-positive bacteria. We further introduce a non-genomic phage engineering method, which adds functionalities for only one replication cycle. In summary, we expect this cell-free methodology to foster reverse and forward phage engineering and customized production of clinical-grade bacteriophages. Graphical abstract: Highlights: Personalized and cell-free production of phages against multidrug-resistant bacteria Extending cell-free production to phages targeting gram-positive bacteria Transient, non-genomic engineering of bacteriophages Time-resolved proteomics during phage assembly and validation of phage proteins Abstract : Emslander, Vogele et al. demonstrate the personalized production of therapeutic bacteriophages in a cell-free system. This approach is faster and safer than the conventional method based on cultivating host bacteria. Cell-free production also allows for time-resolved proteome analysis during phage assembly and biosafe, non-genomic engineering of single-use phages targeting multidrug-resistant bacteria.